2013
DOI: 10.1681/asn.2012050460
|View full text |Cite
|
Sign up to set email alerts
|

Central Body Fat Distribution Associates with Unfavorable Renal Hemodynamics Independent of Body Mass Index

Abstract: Central distribution of body fat is associated with a higher risk of renal disease, but whether it is the distribution pattern or the overall excess weight that underlies this association is not well understood. Here, we studied the association between waist-to-hip ratio (WHR), which reflects central adiposity, and renal hemodynamics in 315 healthy persons with a mean body mass index (BMI) of 24.9 kg/m 2 and a mean 125 I-iothalamate GFR of 109 ml/min per 1.73 m 2 . In multivariate analyses, WHR was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 56 publications
(59 reference statements)
3
60
1
1
Order By: Relevance
“…However, we found no differences in circulating parameters of RAAS activity or in ANG II renal responsiveness. A higher BMI, even in the nonobese (4), and central fat distribution (14) have also been associated with hyperfiltration, but in our study, body fat distribution was similar between the groups, and the slight difference in BMI could not explain the difference in FF, as tested by multivariate analysis. Alternatively, a redistribution of RBF toward juxtacortical glomeruli, with a higher FF, could be present.…”
Section: Discussioncontrasting
confidence: 71%
“…However, we found no differences in circulating parameters of RAAS activity or in ANG II renal responsiveness. A higher BMI, even in the nonobese (4), and central fat distribution (14) have also been associated with hyperfiltration, but in our study, body fat distribution was similar between the groups, and the slight difference in BMI could not explain the difference in FF, as tested by multivariate analysis. Alternatively, a redistribution of RBF toward juxtacortical glomeruli, with a higher FF, could be present.…”
Section: Discussioncontrasting
confidence: 71%
“…55 Other than indirect effects on kidney disease incidence and progression (by type 2 diabetes, atherosclerosis, and hypertension), adiposity may also directly impact kidney function. 56 Indeed, Kwakernaak et al 57 recently reported that a central body fat distribution was associated with an unfavorable renal hemodynamic pattern. As reviewed by Wickman and Kramer, 56 increased fat mass leads to mesangial expansion and increased renal metabolic demand that may promote glomerular hyperfiltration, glomerular hypertrophy, decreased podocyte density, increased foot processes, and increased filtration fraction (i.e., alterations that promote proteinuria and glomerulosclerosis).…”
Section: Obesity-a Preventable Risk Factor For Ckdmentioning
confidence: 99%
“…There are several reports examining the relationship between obesity and renal hemodynamic changes [3,5,6,8,[22][23][24][25][26]. However, the relationship between abdominal fat distribution and glomerular hyperfiltration and has not been studied to date.…”
Section: Introductionmentioning
confidence: 99%